Geological and Geomorphological Context and Characterization of Constructive Materials from the Iberian–Roman Archaeological Site at La Vispesa (NE Spain) - José Luis Peña-Monné; María Marta Sampietro-Vattuone; Elena Maestro-Zaldívar; Almudena Domínguez-Arranz (Heritage)
La Vispesa is an archaeological settlement occupied from the First Iron Age to the Imperial Roman Period. The objectives of this study were to (i) perform a geomorphological characterization of the site; (ii) place it in its regional context; (iii) obtain values of uniaxial compressive strength (UCS) to characterize the construction materials; (iv) assess the chronological data obtained; (v) establish the origin of the sandstones used; and (vi) assess the application of these techniques at archaeological sites. UCS estimations were produced for the preserved walls using a Schmidt hammer, and two groups of samples were identified. In these samples, stones from the Iberian Epoch walls were considerably weathered, while the Roman ashlars were well preserved as they were built from better-quality material that produced high UCS values. In addition, measurements of various sandstone outcrops probably used as quarries were made to compare values. Only one sandstone outcrop had estimations that could relate to the provision of raw material for the Roman period, while other estimations are compatible with Iberian walls. The application of this methodology proves to be highly beneficial for the analysis and comprehension of ancient constructions.